2013
DOI: 10.1002/jbm.a.34800
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive biodegradable PEG‐PCL‐PEG based injectable hydrogel for pulsatile insulin delivery

Abstract: An injectable biodegradable hydrogel was prepared for temperature-responsive pulsatile release of insulin. Triblock copolymer of poly(ethylene glycol)-poly(ε-caprolactone)-poly(ethylene glycol) (PEG-PCL-PEG, PECE) was prepared by ring opening bulk copolymerization and characterized using FT-IR, (1) HNMR, and gel permeation chromatography. Aqueous solution of PECE formed an injectable hydrogel, which was solution at room temperature and transformed into gel at 37°C. The temperature-responsive sol-gel transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 56 publications
0
45
0
Order By: Relevance
“…Therefore, differently from PEG/PCL multiblock hydrogels, gelling mechanism of concentrated solutions of triblock PEG/PCL copolymers may be influenced by crystallization, due to their relatively fast crystallization rate compared to multiblock copolymers. Similarly, Payyappilly et al showed that PECE hydrogels (30 % concentration) partially crystallized, showing a melting peak at around 39°C [Fig. (c)].…”
Section: Physicochemical Propertiesmentioning
confidence: 82%
See 1 more Smart Citation
“…Therefore, differently from PEG/PCL multiblock hydrogels, gelling mechanism of concentrated solutions of triblock PEG/PCL copolymers may be influenced by crystallization, due to their relatively fast crystallization rate compared to multiblock copolymers. Similarly, Payyappilly et al showed that PECE hydrogels (30 % concentration) partially crystallized, showing a melting peak at around 39°C [Fig. (c)].…”
Section: Physicochemical Propertiesmentioning
confidence: 82%
“…Rheological characterization is also helpful to measure the molecular weight of hydrogel chains between the crosslinks ( M c ), according to the following equation: Mnormalc=ρR×T/G where G ′ is the elastic modulus of the linear region of the modulus versus stress sweep plot, ρ is the polymer density, R is molar gas constant, and T is the test temperature. M c decreases with increasing polymer concentration in hydrogel, affecting hydrogel permeability to molecules.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…Hydrogels are finding significant promise as drug delivery vehicle 40. 41 The interstitial space within the fibrillar network of the hydrogel might help in the entrapment of a drug and release it at a rate, which is dependent on the porosity of the hydrogel correlated to the extent of the crosslinked SAFIN 40. 41 Hence, drug diffusion is supposed to be tuned by the degree of swelling of the hydrogel.…”
Section: Resultsmentioning
confidence: 99%
“…41 The interstitial space within the fibrillar network of the hydrogel might help in the entrapment of a drug and release it at a rate, which is dependent on the porosity of the hydrogel correlated to the extent of the crosslinked SAFIN 40. 41 Hence, drug diffusion is supposed to be tuned by the degree of swelling of the hydrogel. To this end, glucose‐stimulated swelling of the LMHG 1 a (as observed from our SEM study), encouraged us to explore its possible application for in vitro drug release through a diffusion pathway 40.…”
Section: Resultsmentioning
confidence: 99%
“…However, the nondegradability and poor in vivo stability of the Pluronics are considered limitations for clinical applications [53]. Recent effort has therefore, been focused on developing biodegradable PEG-based injectable hydrogels with degradable hydrophobic blocks such as poly(ε-caprolactone), polyesters and polyurethanes [5456]. …”
Section: Responsive Hydrogelsmentioning
confidence: 99%